Optimalisasi Pemasaran Digital dalam Meningkatkan Penjualan UMKM Warmindo SR di Yogyakarta - Kholifatun Rosidah; Azfa Mutiara Ahmad Pabulo (Ikatan Da'i Indonesia, 2025)
The community service activity through the student internship program aimed to optimize digital marketing by providing training on social media content creation for the MSME Warmindo SR in Yogyakarta. The main problem faced by the partner was the lack of understanding and skills in producing attractive and consistent social media content as a means of promotion. The implementation methods included initial observation, training on digital content creation (photos, videos, and promotional captions), and one month of mentoring in applying digital marketing strategies. The results of the activity showed an improvement in the partner’s ability to produce engaging promotional content and an increase in consumer interaction through social media. In addition, Warmindo SR’s sales turnover increased after consistently implementing digital promotions. This activity had a positive impact on enhancing the competitiveness and sustainability of MSMEs in the digital era.